Estandarización del tratamiento para la recuperación de crudo a partir de fluido fuera de especificaciones en la estación "A" de un campo situado en el municipio de Puerto Gaitán (2020)
it is raised through the present degree project, the standardization of chemical and thermal treatment applied to those kind of fluids, from the realization of a manual of basic processes based on the facilities, equipment and chemistry available in Station “A”. The validation of the project was carried out based on the characterization of FFE samples corresponding to the TK 1102A/B/D and 1103 A tanks, which were executed in the laboratory under the standards ASTM D70-18a, ASTM D1298-12b, ASTM D4007-11, ASTM D4006-16; Additionally, bottle tests and subsequent field application (Station “A”) of the Operations Manual for the Recovery of Crude from FFE proposed in this project were carried out.